1998
DOI: 10.1590/s0100-84041998000300003
|View full text |Cite
|
Sign up to set email alerts
|

Fungal succession on leaves of Alchornea triplinervia (Spreng.) Muell. Arg. submerged in a stream of an Atlantic Rainforest in the state of São Paulo, Brazil

Abstract: Leaves of Alchornea triplinervia (Spreng.) Muell. Arg. were submerged in a stream in an Atlantic Rainforest in São Paulo state, Brazil, from July/1988 to June/1989 and from July/1989 to May/1990. Fungi were isolated by the leaf disks washing technique followed by plating on culture media and also by using baiting techniques (using substrates with chitin, keratin and cellulose), what resulted on 565 fungal registers corresponding to 81 taxa. The most common species found during this study of the fungal successi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…O predomínio de hifomicetos no folhedo foi observado em pesquisas realizadas no Brasil (Maia 1983;Schoenlein-Crusius & Milanez 1998;Wellbaum et al 1999;Gusmão et al 2001) e em outros países: Porto Rico (Polishook et al 1996), Austrália (Parungao et al 2002) e Costa Rica (Bills & Polishook 1994).…”
Section: Resultsunclassified
“…O predomínio de hifomicetos no folhedo foi observado em pesquisas realizadas no Brasil (Maia 1983;Schoenlein-Crusius & Milanez 1998;Wellbaum et al 1999;Gusmão et al 2001) e em outros países: Porto Rico (Polishook et al 1996), Austrália (Parungao et al 2002) e Costa Rica (Bills & Polishook 1994).…”
Section: Resultsunclassified
“…In the same area, an evaluation of diversity of a soil submitted to high quantities of bird's excrements yielded seven zoosporic fungi, 22 anamorphs, 19 Mucorales and one Ascomycota (41,60). In the preserved forest of the "Reserva Biológica de Paranapiacaba" the study of the fungal succession on Alchornea triplinervia leaves in the terrestrial and aquatic environments resulted in the isolation of 20 zoosporic fungi, 82 anamorphs, 20 Mucorales and eight Ascomycota, a total of 123 fungal taxa (55)(56)(57)(58). Comparison of the aquatic mycota on submerged leaves of Ficus microcarpa L. f., Quercus robur L. and Alchornea triplinervia in a same stream, permitted the observation of 20 zoosporic fungi and 11 aquatic Hyphomycetes (59).…”
Section: Resultsmentioning
confidence: 99%
“…In the State of São Paulo, the diversity of several groups of fungi is better known because surveys have been done in terrestrial and aquatic environments in some preserved or less affected Atlantic Rainforest in protected areas such as "Reserva Biológica de Paranapiacaba" (1,19,23,25,(55)(56)(57)(58)(59)69), "Parque Estadual da Ilha do Cardoso" (66,67,68,71,72) and "Estação Ecológica da Juréia-Itatins" (2,12,22,42), but also in regions relatively close (10 to 20km) to the center of the city of São Paulo, such as "Represa do Guarapiranga" (14,32,50,51,75) and "Parque Estadual das Fontes do Ipiranga", where the Botanical Institute of São Paulo is located (16,17,20,24,(36)(37)(38)(39)(40)(41)(44)(45)(46)54,70,73).…”
Section: Introductionmentioning
confidence: 99%
“…In the "Reserva Biológica do Alto da Serra de Paranapiacaba", municipality of Santo André, many species of aquatic Hyphomycetes were observed during the fungal succession on decomposing submerged leaves of A. triplinervia (51). In the same region, the mycota associated with leaves of Ficus microcarpa, Alchornea triplinervia and Quercus robur were compared, evaluating the diversity (53), the methods for fungal quantification to express the colonization intensity (45) and the correlation between fungal diversity (zoosporic fungi and aquatic Hyphomycetes) and macro and microelements during the decomposition (54,55).…”
Section: Brazilmentioning
confidence: 99%
“…It has been observed that some typical geofungi isolated from such areas, like Epicoccum nigrum Link and Trichoderma viride Rifai are able to produce spores in submerged cultures (51). Beltrania, Camposporium, Chaetendophragmia, Cladosporium, Cryptophiale, Dactylella, Dictyochaeta, Kionochaeta, Phaeoisaria, Subulispora, Tetraploa and other well-known terrestrial genera of Hyphomycetes are usually found on submerged litter as "facultative aquatic fungi" (21).…”
Section: Introductionmentioning
confidence: 99%